LEGAL POLICIES FOR THE PROTECTION OF THE COMMUNITY AS THE OWNER OF TRADITIONAL KNOWLEDGE - Ida Hanifah; Ismail Koto (Journal of Islamic, Social, Economics and Development, 2023)
Until now there is no agreement on the protection of traditional knowledge, especially to indigenous people who are considered the owners of traditional knowledge, this is due to differences in views regarding traditional ownership. then the problem in this research. How is the legal protection of traditional knowledge in Indonesia? What is the legal policy for protecting the community with traditional knowledge? The objectives of this research are as follows. Knowing how the legal protection of traditional knowledge in Indonesia. Knowing the legal policy of protection of the people who have traditional knowledge. The research method used is normative juridical research, namely legal research conducted by examining library materials or secondary data. In Indonesia itself, there is no legal protection that firmly regulates legal protection for people who have traditional knowledge, because the current rules do not provide firm legal protection, the government must take legal policies. In the form of law by making special rules that regulate the legal protection of people who have traditional knowledge and secondly, socializing from the government to people who have traditional knowledge. Suggestions from the authors in this study are that the government in this case is the DPR should be taken seriously in protecting the people who have traditional knowledge by immediately making strict rules showing legal protection so that they are not taken and recognized by other countries.